Metabolic and hematologic changes occurring after rapid intravenous infusion of gammaglobulin in patients with antibody deficiency syndromes - Costa-Carvalho , Beatriz Tavares; Lin, Marisa; Solé, Dirceu; Carneiro-Sampaio, Magda Maria Sales; Sorensen, Ricardo Uhr; Naspitz, Charles Kirov (São Paulo Medical Journal, 1998)
OBJECTIVE: We wished to investigate whether increased IgG infusion rates are associated with metabolic and hematologic changes in pediatric patients with antibody deficiency syndromes. METHODS: We studied 7 patients (2-16 years old) with primary antibody deficiencies who had been on regular IgG replacement treatment, 350-600 mg/kg/dose every 3 weeks with a 3% IVIG preparation, for periods ranging from 6 months to 4 years. Initially, the IgG concentration of IVIG preparations was increased to 6, 9 and 12% in consecutive infusions at a constant IgG infusion rate of 4 mg/kg/min. Subsequently, the infusion rates were increased to 8, 12, and 16 mg/kg/min using the IVIG 12% preparation. RESULTS: Clinically, all patients tolerated increases in IVIG concentrations while the infusion rate was 4 mg/kg/min. However, 3 patients presented side effects when the infusion rate was increased to 8 and 16 mg/kg/min. CONCLUSION: We conclude that metabolic and hematologic sides effects occur with rapid infusion of IVIG even in patients who tolerate the increased infusion rate clinically. The advantages of using high infusion rates have to be re-evaluated.